Lessons from basement inspection cases - Troconis de Rincón, O.; Sánchez, M.; Millano, V.; Bravo, J.; Delgado, S. (Revista ALCONPAT, 2012)
This paper shows the lessons learned in evaluating and diagnosing corrosion and structural problems in several basements of different types of buildings located near and far from the coast. The results of this inspection are reported. They include: damage survey, physicalchemical, mechanical and electrochemical tests; all of which allowed characterizing the concrete and corrosion damages that could compromise the structures evaluated. Since in most cases the basements are used as parking lots, corrosion problems are due, in general, to the carbonation of concrete. However, this effect is potentiated by high freatic levels and the presence of saline water bags located in the subsoil of the basement, which allowed not only the ingress of water but also of chloride ions into concrete. This paper shows the evaluation and recommendations of actions to be taken to extend the service life of the reinforced concrete structures evaluated.